Unifying the current self, ideal self, attributions, self-authenticity, and intended effort: A partial replication study among Chinese university English learners. (December 2020) - Smith, Sara A.; Foster, Matthew E.; Baffoe-Djan, Jessica Briggs; Li, Zhengjie; Yu, Sun
Abstract: There have been increasing calls within the field for greater replication. The current study extends prior work by unifying motivational selves, attributions of learning, and perceptions of suppressed self-authenticity, a topic not previously explored in China. Using confirmatory factor analysis and structural equation modeling (SEM), we examined English learner motivational selves, self-authenticity, and attributions. Young adult learners in rural China (n = 371) completed surveys addressing motivational selves, attributions, self-authenticity (general and in digital environments), L2 English effort, and daily language use. Results replicated those of Henry and Cliffordson (2017) for initial hypotheses related to motivational selves; current and ideal selves were statistically significant predictors of effort, in line with prior studies in the Chinese context. However, results among this sample supported discrete constructs for ideal L2 and current L2 self and provide evidence of a separable sub-component of self-authenticity, digital self-authenticity. In addition, we extend Henry and Cliffordson (2017) by exploring alternative pathways to L2 effort including a unified comprehensive SEM that included ideal L2 self, current L2 self, learning locus, attributions, suppressed self-authenticity. Finally, we discuss implications for specifically addressing digital environments in language learning research.